Intensi Berwirausaha Mahasiswa Universitas Pamulang - Ambar Widya Lestari; Citra Eliyani (Ilmu Sosial, Ekonomi, dan Humaniora, 2024)
The purpose of this research is to determine whether there is an influence of parental background and self-efficacy on the entrepreneurial intentions of Pamulang University students partially and simultaneously. The method used is quantitative with a survey approach. The population in this study were all Pamulang University students for the 2020/2021 academic year. Meanwhile, the sampling technique in this research is based on the non-probability sampling technique (Purposive Sampling), namely purposive sampling. The sample for this research consisted of 300 respondents. This data collection technique uses observation, interviews and questionnaires. The data testing method uses validity testing and reliability testing, the data analysis method uses regression testing and hypothesis testing. The research results show that the self-efficacy variable has an influence on the entrepreneurial intentions of Pamulang University students, as seen from the regression coefficient value of 0.255 (positive) and parental background has an influence on the entrepreneurial intentions of Pamulang University students, as seen from the regression coefficient of 2.447 (positive), indicating that there is a significant influence. positive between parental background variables and entrepreneurial intention variables. And simultaneously the regression coefficient of the independent variable gives a positive value, namely 1.616 (parental background) and 0.183 (self-efficacy) for the dependent variable, namely entrepreneurial intentions. Abstrak Tujuan penelitian ini adalah untuk mengetahui apakah ada pengaruh latar belakang orang tua, dan efikasi diri terhadap intensi berwirausaha  mahasiswa Universitas Pamulang secara parsial dan simultan. Metode yang digunakan adalah kuantitatif dengan pendekatan survey. Populasi dalam penelitian ini adalah seluruh mahasiswa Universitas Pamulang tahun ajaran 2020/2021. Sedangkan teknik pengambilan sampel dalam penelitian ini didasarkan pada teknik sampling Non probability sampling (Purposive Sampling) yaitu sampling purposive .Sampel penelitian ini berjumlah 300 responden. Teknik pengumpulan data ini menggunakan observasi, wawancara serta angket atau kuesioner. Metode pengujian data menggunakan uji validitas dan uji reliabilitas, metode analisis data menggunakan pengujian regresi dan pengujian hipotesis. Hasil penelitian variabel  efikasi diri berpengaruh terhadap Intensi Berwirausaha mahasiswa Universitas Pamulang terlihat dari nilai koefesien regresi sebesar 0, 255 (positif) dan latar belakang orang tua memiliki pengaruh terhadap intensi berwirausaha mahasiswa Universitas Pamulang  terlihat dari koefesien regresi sebesar 2,447 (positif) menunjukkan ada pengaruh yang positif di antara variabel latar belakang orang tua dan variabel intensi berwirausaha. Serta secara simultan Koefesien regresi dari variabel independen memberikan nilai yang positif yaitu sebesar 1,616 (latar belakang orang tua) serta 0,183 (efikasi diri) terhadap variabel dependen yaitu intensi berwirausaha. Kata Kunci: latar belakang orang tua; efikasi diri; intensi berwirausaha